Efficiency enhancing taxation in two-sided markets - Hans Jarle Kind; Marko Koethenbuerger; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper examines the efficient provision of goods in two-sided markets and characterizes optimal specific and ad-valorem taxes. We show that (i) a monopoly may have too high output compared to the social optimum; (ii) output may be reduced by imposing negative value-added taxes (subsidy) or positive specific taxes.
Keywords: D4; D43; H21; H22; L13; 330; Optimale Besteuerung; Subvention; Monopol; Wirtschaftliche Effizienz; Wohlfahrtseffekt; Theorie